78 OUTCOME AFTER ATTEMPTED PERCUTANEOUS INTERVENTION OF CHRONIC TOTAL OCCLUSION USING DRUG-ELUTING STENTS. Issue 1 (1st January 2007) - Khan, Q.; Sachdeva, R.; Reddy, R.; Malhotra, A.; Mehta, J.
Abstract : Background: Chronic total occlusions (CTOs) of coronary arteries present a therapeutic challenge; many of these patients are often referred for bypass surgery, whereas others are left untreated. There are scant data on the outcome of patients treated with percutaneous intervention (PCI) using drug-eluting stents (DESs). Methods: We attempted PCI in 72 patients with CTO with symptoms of ischemia for ≥ 1 year and attempted PCI. All patients were men, age 64 ± 9 years; 41 (57%) had disabling stable angina, 13 (18%) had unstable angina, 15 (21%) had dyspnea, and 3 (4%) had ventricular arrhythmias. Results: Thirteen patients (18%) had single-vessel CAD, 27 (38%) two-vessel CAD and 32 (44%) triple-vessel CAD. Right coronary artery was involved in 33 (45.5%) cases, left anterior descending artery in 15 (21%), left circumflex in 23 (32%), and left main in one (1.5 %). PCI with DES was successful, defined as < 30% residual stenosis and TIMI III flow, in 34 of 72 patients (47%) and not successful in the other 38. There were no procedure-related deaths, but complications included 13 perforations, 6 dissections, and 1 tamponade. At a mean follow-up of 6 months, major adverse cardiovascular events (MACEs: death, myocardial infarction, and repeat revascularization) occurred in 11of 38 (29%) patients in the no-success group and 1 (3%) in the success group ( p < .01) (Figure). Sixteen of 38 (42%) patients in the no-success group continued to have angina compared with 2 (6%) in the success group ( p < .01). Conclusions: PCI of CTOs in the era of DES is relatively safe and leads to significant reduction in MACE, angina, and the need for bypass surgery.